Open & Distance Learning (ODL) and Agricultural Extension Workers’ Social Competence in Indonesia - Nurul Huda (Journal of Education and Learning (EduLearn), 2015)
Social competence is essential for agricultural extension worker since it is directly related to their duties to interact with farmers.   This article discusses the extension to which Open and Distance Learning (ODL) can improve the social competence and its aspects, the dominant factors affecting social competence, and strategy for the development of social competence of extension workers. Designed as an explanatory research, the entire population of agricultural extension workers (n=111) who were graduated from ODL in four different locations (Serang, Karawang, Cirebon, and Tanggamus areas) were used as respondents. A survey technique was implemented among them. In depth interview was also conducted to elaborate the findings. Data was analyzed by using descriptive and regression analysis. The findings indicated that: (1) agricultural extension workers had a moderate level in their social competence. Their knowledge on social concept was relatively good but still having problems in implementing it; (2) learning facilities, training, and subject matter coverage were factors significantly affecting social competence. The most dominant factor was held by the subject matter coverage; and (4) strategies that can be formulated to improve social competence were improving their level of knowledge and skills in terms of social matters. These can be focused on improving the learning quality, mainly on subject matter development. From the findings, it can be concluded that ODL as an educational institution can be addressed by agricultural extension workers to improve their social competence. As an implication, ODL institution need to support the students by giving a better subject matter coverage, while Agricultural Department  need to support the learning quality  of agricultural extension workers  by giving learning motivation and learning facilities.